Exploration of Acetic Acid-Producing Bacteria from Heterotrigona itama Honey in Sukabumi, Indonesia - Ici Dianita; Rika Raffiudin; Anja Meryandini (HAYATI Journal of Biosciences, 2026)
Honey produced by stingless bees is generally characterized by higher acidity, which is associated with organic acid–producing microorganisms, such as lactic acid and acetic acid–producing. These bacteria can survive in this environment due to their tolerance to high sugar concentrations and low pH. Therefore, this study aimed to explore the presence of lactic acid– and acetic acid–producing bacteria and to analyze their relationship with honey sugar, with a particular focus on the characterization of acetic acid–producing bacteria isolated from Heterotrigona itama honey. This study involved characterizing honey for physicochemical properties and sugar content, and isolating bacteria. Additionally, isolates of acetic acid-producing bacteria were selected on selective media, and molecular identification was performed using 16S rRNA gene sequences. The results show that the proportion of lactic acid– and acetic acid–producing bacteria may influence the sugar content of honey. Honey Hi3 exhibited higher electrical conductivity (EC), total dissolved solids (TDS), moisture content, and acidity compared to the other honey samples. A total of 11 selected isolates showed diverse characteristics and were non-hemolytic. Isolate Hi11 produced 0.3% acetic acid over 48 hours and has optimal acetic acid production in glucose, yeast extract, peptone, and ethanol (GYPE1) medium. Based on 16S rRNA gene sequence analysis, this isolate was identified as the genus Enterobacter. These findings indicate the presence of acetic acid–producing bacteria and their potential contribution to the sour sensory characteristics of H. itama honey in Indonesia.